Evaluation of Antibiotic Resistant and Metal Tolerances Capability of Petroleum (hydrocarbon) Degrading Bacteria. Issue 1 (January 2022) - Mohsin, Umema; Lowry, Madan; Devi, Pooja; Dixit, Himanshu; Thakur, Shaile
Abstract: Diesel oil is considered one of the important products of crude oil which constitute a vital source of pollution in the environment. Biodegradation of complex hydrocarbon requires cooperation of more than a single species. This is true in case of pollutants made up of crude oil or petroleum. Soil contains varieties of microorganism that can be established in any natural environment. The bacterial isolates were characterized biochemically by indole test, methyl red test, citrate utilization Test, voges proskauer test, starch hydrolysis, catalase production test, nitrate reduction test, antagonism test, oligodynamic susceptibility and antibiotic sensitivity tests.